Serum ferritin as a diagnostic marker for cardiac iron overload among beta-thalassemia major children - Majhi, Subash Chandra; Mishra, Nihar Ranjan; Panda, Prakash Chandra; Biswal, Sumeet Soumyaranjan (Indian Journal of Child Health, 2019)
Introduction: Beta-thalassemia major is the most common chronic hemolytic anemia. It is a well-comprehended fact that the toxic effects of iron overload particularly the cardiomyopathy are the major complication that roots from beta-thalassemia major children. Therefore, timely diagnosis is crucial to optimize the long-term gain. Objective: The objective of the study is to find the cutoff level of serum ferritin for early diagnosis of cardiac iron overload. Materials and Methods: This study was an observational analytical cross-sectional diagnostic study which was conducted from November 2016 to October 2018. With due approval of Institutional Ethics Committee and after taking proper informed consent from the parents and/or legal heir, 105 thalassemic children were enrolled in the study by simple consecutive sampling after satisfying the pre-defined inclusion and exclusion criteria. In this study, two-dimensional Doppler echocardiography was used to detect cardiac iron overload. Serum ferritin levels were estimated, and cutoff values were calculated for each of the echocardiographic parameters of cardiac iron overload, i.e. ejection fraction (EF), left ventricular end-diastolic diameter (LVEDD), and left ventricular end-systolic diameter (LVESD) by receiver operating characteristic curve analysis. Sensitivity (Sn), specificity (Sp), positive predictive value, and negative predictive value were calculated with considering p<0.05 as statistically significant. Results: The mean age of the study participants was 9±3 years. Cutoff value of serum ferritin for detecting abnormality in EF was 3286 ng/ml with Sn of 76.1% and Sp of 88.1%. Similarly, for detecting abnormal LVEDD, cutoff value of serum ferritin was 4640 ng/ml with Sn of 70.1% and Sp of 98.6%, and for LVESD, it was 3286 ng/ml with Sn of 90% and Sp of 70.5%. Conclusion: The serum ferritin level can be used as a reliable marker of myocardial iron overload among childhood beta-thalassemia and hence can be used as an important screening tool.